A Phase 3, Randomized, Double-Blind, Multicenter Study to Evaluate the Safety and Efficacy of Intravenous Iclaprim Vs Vancomycin for the Treatment of Acute Bacterial Skin and Skin Structure Infections Suspected or Confirmed to be Due to Gram-Positive Pathogens: REVIVE-1. (21st December 2017) - Huang, David B; O'Riordan, William; Overcash, J Scott; Heller, Barry; Amin, Faisal; File, Thomas M; Wilcox, Mark H; Torres, Antoni; Dryden, Matthew; Holland, Thomas L; McLeroth, Patrick; Shukla, Rajesh; et al.
Abstract : Iclaprim achieved noninferiority compared with vancomycin at its primary endpoint of early clinical response in a phase 3 study for the treatment of acute bacterial skin and skin structure infections. Abstract: Background: Our objective in this study was to demonstrate the safety and efficacy of iclaprim compared with vancomycin for the treatment of patients with acute bacterial skin and skin structure infections (ABSSSIs). Methods: REVIVE-1 was a phase 3, 600-patient, double-blinded, randomized (1:1), active-controlled trial among patients with ABSSSI that compared the safety and efficacy of iclaprim 80 mg fixed dose with vancomycin 15 mg/kg, both administered intravenously every 12 hours for 5–14 days. The primary endpoint of this study was a ≥20% reduction in lesion size (early clinical response [ECR]) compared with baseline among patients randomized to iclaprim or vancomycin at the early time point (ETP), 48 to 72 hours after the start of administration of study drug in the intent-to-treat population. Results: ECR among patients who received iclaprim and vancomycin at the ETP was 80.9% (241 of 298) of patients receiving iclaprim compared with 81.0% (243 of 300) of those receiving vancomycin (treatment difference, −0.13%; 95% confidence interval, −6.42%–6.17%). Iclaprim was well tolerated in the study, with most adverse events categorized as mild. Conclusions: Iclaprim achieved noninferiority (10% margin) at ETP compared with vancomycin and was well tolerated in this phase 3 clinical trial for the treatment of ABSSSI. Based on these results, iclaprim appears to be an efficacious and safe treatment for ABSSSI suspected or confirmed to be due to gram-positive pathogens. Clinical Trials Registration: NCT02600611.